Hagop Bogigian of Hussenig - Günaydın, Meryem (Fırat University, 2022)
Hagop Bogigian is the first person to immigrate to America from Huseynik. He is also the “first Armenian-American millionaire”. The story of Bogigian, who set out with the desire to immigrate to America at the age of 19, is of the kind that encourages those who immigrated after him. It is important to follow the traces of his life story even from this aspect alone. It is possible to encounter the characteristic features of the migration movement in many aspects such as the reason for the individual request for immigration, going to America, the aids he received, how and where he settled in America, what he was engaged in. Bogigian, who met the "New World" in Harput under the influence of American missionaries, is not just an ordinary immigrant. Later, as an Armenian-American importer and exporter, he transferred technological innovations to the Ottoman lands, especially to the east. He used all his political and financial means and connections to the Armenian immigrants who came to America like him. Again, the thought and work of Armenians living in a designated area in Canada and America with the idea of an "Armenian colony" is remarkable. After his death, he left his legacy as the “Hagop Bogigian Scholarship Fund” to the education of Armenian students in need, especially women, at Wilson College, Mount Holyoke College and Pomona College. The life story of Hagop Bogigian, whose footprints of the first Armenian migration from Hüseynik to America will be traced, is the subject of this study. Bogigian's life is also a representative story that carries important clues to understand the transatlantic migration that started from Harput.

Hagop Bogigian Hüseynik’ten Amerika’ya ilk göç eden kişidir. Aynı zamanda “ilk Ermeni-Amerikalı milyoner”dir. 19 yaşında Amerika’ya göç etmek arzusu ile yola çıkan Bogigian’ın öyküsü kendinden sonra göç edenleri teşvik eden türdendir. Bir tek bu yönüyle dahi onun hayat öyküsünün izlerini sürmek mühimdir. Münferit olarak göç isteğinin sebebi, Amerika’ya gidişi, aldığı yardımlar, Amerika’da nasıl ve nerede yerleştiği, ne işle meşgul olduğu gibi birçok hususta göç hareketine ilişkin karakteristik özelliklere rastlamak mümkündür. Harput’ta Amerikan misyonerlerinin tesiriyle “Yeni Dünya” ile tanışan Bogigian aslında sıradan bir göçmen değildir. Sonradan Ermeni-Amerikalı bir ithalatçı ve ihracatçı olarak Osmanlı topraklarına özellikle doğuya teknolojik yenilikler transfer etmiştir. Kendisi gibi Amerika’ya gelen Ermeni göçmenlere gerek siyasi gerek mali bütün imkanlarını kullanmıştır. Yine “Ermeni kolonisi” kurmak düşüncesiyle Ermenilerin kendilerine tahsis edilmiş bir mahalde yaşamalarına ilişkin düşüncesi ve çalışmaları dikkat çekicidir. Ölümüyle birlikte mirasını “Hagop Bogigian Burs Fonu” olarak Wilson Koleji, Mount Holyoke Koleji ve Pomona Koleji'nde ihtiyaç sahibi Ermeni öğrencilerin özellikle kız çocuklarının eğitimlerine bırakmıştır.
HÜSEYNİKLİ HAGOP BOGİGİAN